2006
DOI: 10.1016/j.rmed.2005.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mechanisms of macrolides in cystic fibrosis

Abstract: Several studies have reported clinical improvements in cystic fibrosis (CF) patients on macrolide antibiotics although the mechanism of action remains unclear. We conducted an open-label study of azithromycin (500 mg daily for 2 weeks) in 9 adult CF patients to explore 3 possible mechanisms: up-regulation of the multi-drug resistance (MDR) or cystic fibrosis transmembrane regulator (CFTR) proteins, correction of epithelial ion transport and reduced bacterial adherence. End-points included nasal potential diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…However, it has been clearly demonstrated that the apparent beneficial effects of these drugs on pulmonary outcome in CF are not mediated by modulation of ion transport [ 34 ]. An open-label study [ 35 ] concluded that neither up-regulation of multi-drug resistance or CFTR proteins nor reduced bacterial adherence appear to be significant contributing mechanisms accounting for the beneficial results in clinical trials of macrolides in CF. We show that treatment with the macrolide in CF mice attenuated cellular infiltration in spontaneous and induced inflammatory conditions and inhibited pro-inflammatory cytokine release in LPS-induced inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been clearly demonstrated that the apparent beneficial effects of these drugs on pulmonary outcome in CF are not mediated by modulation of ion transport [ 34 ]. An open-label study [ 35 ] concluded that neither up-regulation of multi-drug resistance or CFTR proteins nor reduced bacterial adherence appear to be significant contributing mechanisms accounting for the beneficial results in clinical trials of macrolides in CF. We show that treatment with the macrolide in CF mice attenuated cellular infiltration in spontaneous and induced inflammatory conditions and inhibited pro-inflammatory cytokine release in LPS-induced inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, macrolides reduce sputum viscoelasticity and airway adhesion of P. aeruginosa [189][190][191]. Moreover, they reduce inflammatory response in CF [36, 86,[192][193][194]. Several studies using macrolides either in short-term or in long-term administration have provided positive results regarding reduction of exacerbations and stabilising or increasing respiratory capacity (Table 2) [52, 67,.…”
Section: Macrolides and Cystic Fibrosismentioning
confidence: 99%
“…Subsequent studies indeed showed that macrolides decrease secretion of chemokines such as IL-8 and pro-inflammatory cytokines such as TNF-α in tissue culture and animal models, which do not depend on their antimicrobial activities [164][165][166][167]. The actual mechanisms of these effects and the relevance of individual mechanisms of action in vivo have not yet been fully elucidated, however.…”
Section: Anti-inflammatory Therapy In Cfmentioning
confidence: 99%